Optimization of Agricultural Land: A Lesson from Islamic Economics - Ismail, Nurizal; Aisyah, siti (AL-IKTISAB: Journal of Islamic Economic Law, 2017)
Human as social being is required to earn the wealth obtained from factors of production to survive in his life. One of the important factors is land, which has been mostly used in economy such as infrastructure, agriculture and mining. Unfortunately, the use of land tends to give more benefit to capitalist or land-owner than others in todays’ world. It impacts to inequality distribution of income in the society faced in third world country that is mostly in Muslim countries. In Islam, administration of the land has been concerned in primary sources (Qur’an and Sunnah) and Islamic literatures and practiced into action in the state such as iqta, ihya al-mawat, zakah, rikaz, muzara’ah, salam, musaqah and other instruments. These instruments are mostly used in agricultural field in the Islamic age. Another instrument can contribute to sustainable agricultural development is tax land: al-kharaj and al-’usyr. However, the result of this study states that to optimize the agricultural land, the state and Islamic banks can contribute together to solve the farmers problem such lack of financial support, shortage of water irrigation, lack of training and technology use by integrating appropriate Islamic financing and police of land tax that gives benefit and just to the farmers.